The incidence of feline injection site sarcomas in the United Kingdom - Dean, Rachel S (BioMed Central, 2013)
BACKGROUND: Feline injection site sarcomas (FISS) are aggressive neoplasms that have been associated with vaccination. In North America the incidence estimates have varied from 1 case of FISS per 1,000-10,000 cats vaccinated. The aim of this study was to estimate the incidence of FISS in the United Kingdom (UK) in 2007. The ratio of FISS to vaccines sold in the UK was also estimated. Fourteen FISS were diagnosed by a convenience sample of 34 small animal veterinary practices in the United Kingdom in 2007 and were used as the numerator for the incidence estimates. Denominator data was obtained from the computer systems of each practice. Considering that a single cause relationship with vaccination is not proven, three different denominators (number of cats registered, the number of cat consultations undertaken and the number of vaccination visits for cats at the practices) were used to express the potential variation in risk. RESULTS: The incidence risk of FISS per year was estimated to be 1/16,000 -50,000 cats registered by practices, 1/10,000-20,000 cat consultations and 1/5,000-12,500 vaccination visits. CONCLUSION: When interpreting these findings, it needs to be taken into consideration that this sample of practices and their cats may not be representative of veterinary practices and cats at risk of FISS in the UK. However it can still be concluded with reasonable certainty that the incidence of FISS in the UK is very low.